Beta-adrenergic agonists alter glucose and mitochondrial metabolite utilization independent of a fiber type shift - Munk, Sidney Anne (My University, 2025)
A growing population with diminishing agricultural inputs calls for the livestock industry to incorporate strategies for greater production efficiency. Understanding the biochemical pathways that skeletal muscle utilizes to metabolize nutrients in livestock species can aid in this effort. To investigate changes that occur as the metabolic profile of skeletal muscle shifts, we supplemented pigs with the beta-adrenergic agonist ractopamine hydrochloride (BAA). This pharmacological agent provides an ideal model to induce a metabolic shift without altering genetics, nutrition, or management strategy. Therefore, the objective of this study was to define the BAA-mediated metabolic response in skeletal muscle with inherently different metabolic profiles through assessing changes in myosin heavy chain (MyHC) isoforms, metabolic enzymes, and metabolite utilization. Mature DNA 600 x 241 barrows (DNA Genetics) were fed a standard commercial diet containing 16% crude protein supplemented with 0 g/ton (control; n = 8) or 9 g/ton ractopamine hydrochloride (BAA; n = 10) for 2 weeks. Samples were collected from the longissimus dorsi (LD, glycolytic muscle), latissimus dorsi (LAT, mixed muscle), semitendinosus (ST, mixed muscle), and masseter (MS, oxidative muscle). To determine if BAA feeding induced changes in fiber type, MyHC isoforms were measured because this approach is the traditional method of muscle fiber type classification. Although there were muscle differences in MYH7, MYH2, MYH1, and MYH4 isoforms (muscle; p < 0.05), there were no treatment differences (p > 0.05). The half-life of myosin is approximately the duration of BAA feeding, which may partially explain the lack of BAA induced changes in MyHC isoforms. Therefore, we evaluated glycolytic and oxidative enzymes to assess metabolic adaptations that may occur without altering MyHC isoforms present. While there were differences in PFK activity, LDH[alpha] protein abundance, or SDH[alpha] protein abundance between muscles evaluated (p < 0.05), there were no treatment differences (p > 0.05). However, abundance of PC decreased in all BAA muscles compared to control muscles (p < 0.05), which suggests BAA feeding may diminish oxidation of the glycolytic end product pyruvate. To investigate changes in glycolytic flux, concentrations of glucose, G6P, and lactate were measured. In addition to differences in these glycolytic intermediates across muscles, glucose and G6P decreased in all BAA muscles compared to control muscles (p < 0.05). However, lactate concentration did not differ between BAA and control muscles suggesting BAA feeding prioritizes the utilization of diminished glycolytic intermediates in the Cori cycle. To determine if BAA mitochondria decrease pyruvate oxidation, isolated mitochondria were incubated with ¹³C₃-pyruvate. These data indicate changes in the amount of an isotopomer derived from pyruvate rather than the total amount of an intermediate present. Isotopic enrichment of oxaloacetate (OAA) M + 2 increased in BAA LAT mitochondria compared to control LAT (p < 0.05). In addition, OAA M + 2 increased in BAA LAT mitochondria compared to control and BAA MS mitochondria (muscle * treatment; p < 0.05). In addition, citrate M + 2, M + 3, M + 4, and [alpha]-ketoglutarate M + 4 and M + 5 enrichment decreased in BAA LAT mitochondria compared to all other mitochondria (p < 0.05). Further, citrate M + 6 and [alpha]-ketoglutarate M + 2 and M + 3 enrichment decreased in BAA mitochondria (p < 0.05). Collectively, these data demonstrate BAA supplementation induced changes in glucose utilization independent of frequently measured indicators of metabolic shifts.
Keywords: Metabolism; Muscle biology; Skeletal muscle; Mitochondria